Over a million students use our free study notes to help them with their homework
First we need to start by multiplying the brackets on the right, which will give us:2x^2 + x = x^2 - 4x - 4Then we need to move everything that is on the right to left:2x^2 + x - x^2 + 4x + 4 = 0Here a co...
Always draw a diagram first to help with clarity.Correct use of Sine Rule:sin(A)/BC = sin(C)/ABTherefore sin(C) = ABsin(A)/BC sin(C) = 20sin(70)/100 sin(C) = 0.188 (rounded to 3 Significant Figures) C = a...
5/6 + 3/7= ((5 x 7) + (3 x 6))/(6 x 7)= (35 + 18)/42= 53/42= 1 11/42
7x + 6 = 1 + 2x7x + 6 -2x = 15x + 6 = 15x = 1-65x = -5x = -1
On the first look, you may think that this question looks a bit complex, but if you have ,mastered the basics then you will have absolutely no trouble! Before you jump into this question, you should start...
←
392
393
394
395
396
→
Internet Safety
Payment Security
Cyber
Essentials